Các yếu tố tác động đến kết quả xuất khẩu của các doanh nghiệp thủy sản tại vùng Đồng bằng sông Cửu Long - Lê Tấn, Bửu; Nguyễn Viết, Bằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The paper aims at defining and measuring key factors which impact on export performance of seafood firms in Mekong Delta region by applying qualitative and quantitative methods. The qualitative method is carried out through a discussion group of 10 chief executive officers, while the quantitative one is conducted through direct interviews with 187 managers of seafood companies. The results show that firm's export performance is under the direct influences of seven factors including: (1) Export marketing strategy; (2) Firm's characteristic and capability; (3) Industry characteristics; (4) Management characteristics; (5) Domestic market characteristics; (6) Foreign market characteristics; and (7) Export barriers
Keywords: Export performance; Export seafood; Seafood; Export barriers